1988
DOI: 10.1128/jb.170.3.1168-1174.1988
|View full text |Cite
|
Sign up to set email alerts
|

New loci required for Streptomyces coelicolor morphological and physiological differentiation

Abstract: Streptomyces coelwcolor colonies differentiate both morphologically, producing aerial spore chains, and physiologically, producing antibiotics as secondary metabolites. Single mutations, which block both aspects of differentiation, define bld (bald colony) genes. To identify new bld genes, mutagenized colonies were screened for blocks in the earliest stage of sporulation, the formation of aerial mycelia, and blocks in antibiotic synthesis. The mutations in 12 mutants were mapped; in each strain, the pleiotropi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
144
0
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(149 citation statements)
references
References 19 publications
4
144
0
1
Order By: Relevance
“…In this regard, BldB has been characterized as a protein involved in aerial hyphae formation. 114 Interestingly, it has been observed that after rapid growth has ceased, culture supernatants become protein rich, supporting the idea that protein secretion is also a stationaryphase phenomenon. 116 It is known that on different carbon sources, BldB null mutants have a bald phenotype, that is, lacking an obvious aerial mycelium, are pleiotropically blocked for antibiotic biosynthesis 110 and defective in CCR.…”
Section: Streptomycesmentioning
confidence: 84%
See 3 more Smart Citations
“…In this regard, BldB has been characterized as a protein involved in aerial hyphae formation. 114 Interestingly, it has been observed that after rapid growth has ceased, culture supernatants become protein rich, supporting the idea that protein secretion is also a stationaryphase phenomenon. 116 It is known that on different carbon sources, BldB null mutants have a bald phenotype, that is, lacking an obvious aerial mycelium, are pleiotropically blocked for antibiotic biosynthesis 110 and defective in CCR.…”
Section: Streptomycesmentioning
confidence: 84%
“…Repression is partially relieved using alternative carbon sources (arabinose, galactose, glycerol, mannitol and maltose) for bldA and bldG mutants and totally relieved for bldH mutants. 114 Therefore, all bld mutants isolated, exhibit carbon source-dependent differentiation.…”
Section: Streptomycesmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigation of RNase E activity in Streptomyces mutants blocked at various stages of development provided further evidence of developmentally regulated genetic control of RNase ES; such mutations have mostly been isolated in S. coelicolor A3(2), which is closely related genetically to S. lividans, and their phenotype effects have been well characterized (Chater, 1993): bld mutants do not produce visible aerial mycelia and are also blocked in their physiological differentiation (Merrick, 1976;Champness, 1988;Chater, 1993); whi mutants cannot make mature spores, yielding S. coelicolor colonies that have a whitish, rather than grey, appearance (Hopwood et al, 1970;Chater, 1972). We studied two S. coelicolor bld mutants [bldA (J1700) (Merrick, 1976;Lawlor et al, 1987), bldC (J660) (Merrick, 1976)] and three whi mutants [whiB (Chater, 1972), whiJ (C77) (Chater, 1989) and whiG (C71) (Chater, 1972)] and their parental strains lacking these mutations ( activity increased in the parental S. coelicolor strains, the three whi mutants studied, and a bldC mutant as these various bacteria progressed through their life cycle in solid media (shown only for whiG, Fig.…”
Section: Resultsmentioning
confidence: 99%